Usefulness of Clinical Lectures in First Two Years of Integrated Teaching; Student’s Perspective - Aashi Ahmed, Anwar Bibi, Nadia Nisar, Roma Salman, Raheela Yasmin, Ummara Aslam (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Integrating clinical content into problem-based learning tutorials is associated with learning motivation of undergraduate medical students. Medical students are being exposed to clinical lectures and rotations starting from 1st year in most of the medical colleges across Pakistan. Aim: To determine perspective of 1st and 2nd Year MBBS students regarding clinical lectures as part of integrated teaching. Study Design: Cross-sectional study Place and Duration of Study: HITEC Institute of Medical Sciences, Taxila from 1st July 2021 to 31st December 2021. Methodology: One hundred and seventy eight students of 1st and 2nd year were enrolled. Students who attended clinical lectures for last three months were randomly selected in this study. Structure proforma having ten items scored on five-point Likert scale was used to collect data. Data was analyzed using SPSS version 28. Frequencies were calculated for categorical variables, whereas mean and standard deviation was calculated for continuous variables (age). Results: Eighty (44.9%) were males and 98 (55.1%) were females. Ninety eight (55.1%) were from first year and 80 (44.9%) were from second year. Integration of clinical lectures in early years was reported to help in concept building by 46.6% (n=83, strongly agree) students. According to 45.5% (n=81) students, integration of clinical content makes learning interesting. Median score calculated for the participant’s perception about role of integrated teaching in stimulating interest, concept building, passing exams, ease of schedule was 4 which suggested that majority of the participants agreed to it. Conclusion: Our data showed that early clinical exposure through lectures and clinical rotation stimulates interest in learning by concept building and helps medical students to perform better in their professional examinations. Keywords: Medical education, Integrated curriculum, Early clinical exposure, Students perception